SYSTEMS FOR THE DEVELOPMENT OF THE GOAT REARING SECTOR FOR MILK PRODUCTION - Grigore BALTAG; Alexandru OSOIANU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Along with the increase in the number of animals, the number of animal farms specialized in the production of goat milk also increased, the number of farms equipped with mechanized milking systems, milk pasteurization lines, pasteurized milk bottling, combined slaughterhouses, etc. increased. The aim of the paper is to demonstrate sustainable development as one of the current requirements of the economic efficiency of livestock farms, by ensuring the complete value chain with complex and perfect inputs. The methods of observation, monograph and comparison were used in the elaboration of this work. The data presented in the respective work were accumulated from the statistical researches of the husbandry entities in the country, the official data of the National Bureau of Statistics of Moldova and from the dedicated works on this topic. The results pursued in this research point to the identification of the economic capacities of the goat breeding sector in the Republic of Moldova by making investments in the dimension of increasing the gross added value of the business. The research conclusions allow us to state the availability of reserves by tracking the quality and quantity of production determined by increasing the contribution to the value of production.